2021
DOI: 10.1038/s41598-021-81680-z
|View full text |Cite
|
Sign up to set email alerts
|

Precious metals recovery from aqueous solutions using a new adsorbent material

Abstract: Platinum group metals (PGMs) palladium, platinum, and ruthenium represent the key materials for automotive exhaust gas treatment. Since there are no adequate alternatives, the importance of these metals for the automotive industry is steadily rising. The high value of PGMs in spent catalysts justifies their recycling. Therefore, it is really important to recovery platinum group metals from aqueous solutions. Of the many PGMs recovery procedures, adsorption is a process with a good efficiency, but an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Similar results were found for Chitosan‐DB18 C6 sorbents. The PSO kinetic model fitted better sorption of Pt(IV), Pd(II) than PFO [30] …”
Section: Resultsmentioning
confidence: 96%
“…Similar results were found for Chitosan‐DB18 C6 sorbents. The PSO kinetic model fitted better sorption of Pt(IV), Pd(II) than PFO [30] …”
Section: Resultsmentioning
confidence: 96%
“…Spectral characterization indicated that the cyano group before cross-linking was converted into an amide functional group, which can reduce and adsorb Au or gold chloride complexes well . The chitosan-DB18C6 (CH-DB18C6) material prepared by impregnation with dibenzo-18-crown ether can be used for the recovery of PGMs ions . Among them, CH-DB18C6 has the highest adsorption capacity for Ru­(III) ions, which can be described by a pseudo-second-order model.…”
Section: Strategies For Separation and Restoration Of Pm Ionsmentioning
confidence: 99%
“…68 The chitosan-DB18C6 (CH-DB18C6) material prepared by impregnation with dibenzo-18-crown ether can be used for the recovery of PGMs ions. 69 Among them, CH-DB18C6 has the highest adsorption capacity for Ru(III) ions, which can be described by a pseudo-second-order model. Emergence of MOF Materials.…”
Section: Recoverymentioning
confidence: 99%
“…Grad and coworkers developed dibenzo-18-crown-6-ether-modified chitosan sorbents to remove palladium and platinum species. These sorbents can adsorb more Pd(II) ions with increasing temperature [58]. On the other hand, the thermodynamic adsorption parameters are also dependent on temperature [59], where the uptake capacity increases with increasing temperature for such endothermic processes.…”
Section: Temperaturementioning
confidence: 99%